Strategie rozvoje malé firmy - Horňák, Matej (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Táto diplomová práca sa zaoberá spracovaním analýzy Two Nations s.r.o. a navrhnutím jej stratégie rozvoja. Silné a slabé stránky, príležitosti a hrozby sú sumarizované v kapitole SWOT analýza. Záverečná časť práce determinuje riziká a hodnotí projekt.

This thesis deals with processing of analysis Two Nations Limited Company and suggests strategy for its development. Strengths and weaknesses, opportunities and threats of an enterprise are summarized in a chapter that deals with SWOT analysis. The final part of this thesis determines contingencies and appreciates project.
The small business strategy
Keywords: analýza; firma; obchod; rozvoj; stratégia; analysis; business; development; enterprise; strategy